From extractivism towards buen vivir: mining policy as an indicator of a new development paradigm prioritising the environment. Issue 6 (3rd June 2017) - Broad, Robin; Fischer-Mackey, Julia
Abstract: This article analyses mining policy as an indicator of a larger question: are some Third World governments starting to steer away from plunder 'extractivism' towards a paradigm that prioritises the environment? We begin with the cases of El Salvador and Costa Rica, which have major mining bans in place. We then present the results of our research in which we find five other countries with noteworthy mining-policy shifts: Panama, Colombia, Argentina, Chile, and New Zealand. A sixth country, Honduras under President Zelaya, stands as a recent historical case of how sensitive such a policy change can be. A key take-away from our article is that critical development scholars and practitioners need to look more closely at the mining sector – not simply to analyse case studies of specific mining protests and resistances to extractivism, although these are of course important. Rather, there is a need to investigate policy changes that just might be indications that the era of unquestioning extractivism has ended and that at least some governments are initiating policies to incorporate environmental externalities, policies that suggest a changing development paradigm in the direction of environmental – and concomitant social and economic – 'well-being' as envisioned in buen vivir.